Effect of Service Quality, Facilities and Location on Patient Satisfaction in RSU Sari Mutiara Lubuk Pakam - Iwiwi Sihombing; Nora Anisa Br. Sinulingga (SEAN Institute, 2021)
This study aims to determine: (1) Does the quality of service affect patient satisfaction at Sari Mutiara Lubuk Pakam General Hospital? (2) Does the facility affect patient satisfaction at Sari Mutiara Lubuk Pakam General Hospital? (3) Does location affect patient satisfaction at Sari Mutiara Lubuk Pakam General Hospital? (4) Does the quality of service, facilities and location simultaneously affect patient satisfaction at Sari Mutiara Lubuk Pakam General Hospital?. The method used in this research is quantitative descriptive method. Meanwhile, data collection using questionnaires and documentation. The sampling technique used was accidental sampling technique. This study used a sample of 100 respondents. The instrument testing technique in this study is validity and reliability testing and hypothesis testing using multiple linear regression and classical assumption testing with SPSS version 20 software. The results of this study indicate that: (1) Service quality affects patient satisfaction at Sari Mutiara Lubuk Pakam Hospital, (2) facilities affect patient satisfaction at Sari Mutiara Lubuk Pakam Hospital, (3) location affects patient satisfaction at Sari Mutiara Lubuk Hospital Pakam, (4) service quality, facilities and location simultaneously influence patient satisfaction at Sari Mutiara Lubuk Pakam Hospital. And the results of this study also indicate that the variable that most influences patient satisfaction is the variable of service quality (X1).